2001
DOI: 10.1021/bi011682l
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Incision of an AP Site within Clustered DNA Damage by the Major Human AP Endonuclease

Abstract: A major DNA lesion induced by ionizing radiation and formed on removal of oxidized base lesions by various glycosylases is an apurinic/apyrimidinic site (AP site). The presence of an AP site within clustered DNA damage, induced following exposure to ionizing radiation or radiomimetic anticancer agents, may present a challenge to the repair machinery of the cell, if the major human AP endonuclease, HAP1, does not efficiently incise the AP site. In this study, specific oligonucleotide constructs containing an AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 38 publications
7
58
0
Order By: Relevance
“…Many evidence clearly demonstrated that complex DNA lesions are more dif2icult for the cellular machinery to repair than are individual damage sites (28)(29)(30)(31)(32)(33) . With synthetic oligonucleotides containing several types of DNA damage, David-Cordonnier et al demonstrated that the ef2iciency of incision of an AP site within a region of clustered DNA damage is signi2icantly reduced by the presence of a second AP site or SSB (28) .…”
Section: The Biological Effects Of Hze Particlementioning
confidence: 99%
See 2 more Smart Citations
“…Many evidence clearly demonstrated that complex DNA lesions are more dif2icult for the cellular machinery to repair than are individual damage sites (28)(29)(30)(31)(32)(33) . With synthetic oligonucleotides containing several types of DNA damage, David-Cordonnier et al demonstrated that the ef2iciency of incision of an AP site within a region of clustered DNA damage is signi2icantly reduced by the presence of a second AP site or SSB (28) .…”
Section: The Biological Effects Of Hze Particlementioning
confidence: 99%
“…With synthetic oligonucleotides containing several types of DNA damage, David-Cordonnier et al demonstrated that the ef2iciency of incision of an AP site within a region of clustered DNA damage is signi2icantly reduced by the presence of a second AP site or SSB (28) . Several studies also have shown APs or 8 -oxoguanine (8-OxoG) sites within clustered DNA damage sites are poorly handled by mammalian cell extracts or puri2ied repair DNA damage site which is defined as mul ple lesions within a region of a few nm.…”
Section: The Biological Effects Of Hze Particlementioning
confidence: 99%
See 1 more Smart Citation
“…Alkaline-labile sites (ALS) [60] including AP sites [13,14] lead to DNA strand cleavage at high pH, and alkaline-based SSB assays are at considerable risk of overestimation of SSB. The comet assay performed at pH 12.1-12.5 has been reported to detect SSB without the contamination of artifactual SSB from cleaved ALS; however, this modification has also been reported to reduce the sensitivity of that assay [61].…”
Section: Alkaline-based Single-strand Break Assaymentioning
confidence: 99%
“…SSB is one of the most frequent DNA lesions, and they are produced daily in nuclei during DNA repair processes such as base excision repair (BER) [12]. It is a primary response pathway for the repair of deleterious DNA lesions including non-bulky DNA adducts, apurinic/apyrimidinic (AP) sites [13,14], and SSB. From a chemical point of view, the abasic site is an alkaline-labile residue that leads to strand breaks through beta-and delta-elimination [15].…”
Section: Introductionmentioning
confidence: 99%